The Pengaruh Pendidikan Kesehatan Video Animasi Tentang Hiv/Aids Terhadap Pengetahuan, Sikap Dan Perilaku Remaja Di Ma Mafaza Bantul Yogyakarta - Endar Timiyatun; Eka Oktavianto (LPPM ITEKES Mahardika, 2025)
The problem of HIV/AIDS in adolescents not only has a negative impact mentally and emotionally, but can also have a negative impact on physical health, the immune system in the body and if not treated properly it will cause death. This not only affects the adolescents themselves, but also on families, communities, and nations. This research method uses a one group pretest posttest design. The sampling technique used is total sampling obtained as many as 27 people. Data collection techniques using questionnaires on knowledge, attitudes and behavior. Before the data analysis test, a normality test was carried out using the Shapiro Wilk test and an analysis test for knowledge, attitudes and behavior using the Paired T-Test. The results of the study showed that there was an effect of providing health education with animated videos on knowledge, attitudes and behavior with a P value = 0.000 (p value < 0.05). The modules and videos from this research can be used as educational media for adolescents to increase adolescent knowledge about HIV/AIDS.